2002
DOI: 10.1038/nature01209
|View full text |Cite
|
Sign up to set email alerts
|

Active transport of Ca2+ by an artificial photosynthetic membrane

Abstract: Transport of calcium ions across membranes and against a thermodynamic gradient is essential to many biological processes, including muscle contraction, the citric acid cycle, glycogen metabolism, release of neurotransmitters, vision, biological signal transduction and immune response. Synthetic systems that transport metal ions across lipid or liquid membranes are well known, and in some cases light has been used to facilitate transport. Typically, a carrier molecule located in a symmetric membrane binds the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
131
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(142 citation statements)
references
References 9 publications
4
131
0
7
Order By: Relevance
“…The mechanism of Ca 2þ transfer by this compound is achieved through a redox switching mechanism, principally similar to the redox-dependent proton transfer. 19 In addition to this study, we recently also showed that 2PHQ can transfer not only Ca 2þ but also Ba 2þ , Sr 2þ , and to a lower extent Mg 2þ across mimetic biomembranes. 20 The analysis of the mechanism and the stoichiometry of complex formation revealed that ion binding and transfer depend critically on the adjacent position of the two oxygen atoms in the 2PHQ molecular structure.…”
Section: ' Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The mechanism of Ca 2þ transfer by this compound is achieved through a redox switching mechanism, principally similar to the redox-dependent proton transfer. 19 In addition to this study, we recently also showed that 2PHQ can transfer not only Ca 2þ but also Ba 2þ , Sr 2þ , and to a lower extent Mg 2þ across mimetic biomembranes. 20 The analysis of the mechanism and the stoichiometry of complex formation revealed that ion binding and transfer depend critically on the adjacent position of the two oxygen atoms in the 2PHQ molecular structure.…”
Section: ' Introductionsupporting
confidence: 63%
“…20 The analysis of the mechanism and the stoichiometry of complex formation revealed that ion binding and transfer depend critically on the adjacent position of the two oxygen atoms in the 2PHQ molecular structure. 19,20 Such an arrangement of neighboring oxygens is, however, not found in any naturally occurring CoQ compounds. Consequently, CoQs are known not to bind Ca 2þ and correspondingly do not transport Ca 2þ across membranes.…”
Section: ' Introductionmentioning
confidence: 96%
“…Liposomes,9 where a lipid bilayer separates the inner content from the outer solution, have been used as model systems to couple light energy to different biochemical reactions. The proton gradient developed by a light‐sensitive component, either bacteriorhodopsin or an artificial photosynthetic reaction center, has been coupled to Ca 2+ active transport,10 to ATP synthesis9b or to activate bacterial pumps 11. Liposomes are fragile, however, and increased robustness is desired for in vitro applications that require coupling artificially generated electrochemical gradients to solid transducers, such as lab‐scale biosensors and biomimetic fuel cells.…”
mentioning
confidence: 99%
“…3 Liposomes are also suitable for membrane immobilization of lipophilic quinones. In this context, Bennett et al 10 have recently incorporated the synthetic 2-palmitoylhydroquinone (H 2 Q) in a liposome membrane to build an artificial light-driven transmembrane calcium pump. Although the redox chemistry of H 2 Q is hardly known, these authors have utilized its redox sensitivity to analyze binding of Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%